2022
DOI: 10.1021/acs.est.1c04512
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Organic Matter Characteristics on Fe(II) Oxidation Kinetics in Coastal Seawater

Abstract: The iron­(II) oxidation kinetic process was studied at 25 stations in coastal seawater of the Macaronesia region (9 around Cape Verde, 11 around the Canary Islands, and 5 around Madeira). In a physicochemical context, experiments were carried out to study the pseudo-first-order oxidation rate constant (k′, min–1) over a range of pH (7.8, 7.9, 8.0, and 8.1) and temperature (10, 15, 20, and 25 °C). Deviations from the calculated k cal ′ at the same T, pH, and S were observed for most of the stations. The measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…The preliminary results showed that the effects of salinity on most spectroscopic characteristics were lower than 10% (Figure S1). As such effects were relatively small, we conducted direct measurements on the filtered and diluted water samples (DOC < 5 mg L –1 and salinity <10) according to the previous studies of saline lake water and seawater ,, without using a further desalination approach.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary results showed that the effects of salinity on most spectroscopic characteristics were lower than 10% (Figure S1). As such effects were relatively small, we conducted direct measurements on the filtered and diluted water samples (DOC < 5 mg L –1 and salinity <10) according to the previous studies of saline lake water and seawater ,, without using a further desalination approach.…”
Section: Methodsmentioning
confidence: 99%
“…The dissolved ligands could affect the solubility, reactivity, bioavailability of Fe in natural water, and the primary productivity, i.e., iron biogeochemical cycle, which is crucial to many environmental processes . Via natural or anthropogenic inputs, 3 sources (biological productivity, , siderophores, and synthetic chelators), 6 kinds (amino acid, mono- and poly saccharide, phenols, nitrogen metabolites, porphyrin, and amino-polycarboxylate), and 12 species coexist in DOM as the main ligands. …”
Section: Introductionmentioning
confidence: 99%
“…These ligands are often divided into two types in typical detection, i.e., strong and weak ligands; strong ligands are generally specific inductive ligands with a low concentration level (∼10 –10 mol/L) in the ocean, , and weak ligands are the main type. , The current dFe speciation is determined by competitive ligand exchange/adsorption (according to complexation equilibrium constant) and molecular-level characterizations. , In the aqueous phase, the complexation equilibrium constant can reflect the order and degree of metal binding to different ligands at a certain pH 1 . All of them require instruments (electrochemistry and liquid chromatography mass-spectrometry) and complicated pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations